Laparoscopic Appendectomy in Children: Preliminary Study in Pediatric Hospital Albert Royer, Dakar - Mbaye Fall; Doudou Gueye; Ibrahima Bocar Wellé; Faty Balla Lo; Aloise Sagna; Marie Diop; Ibrahima Fall (Gastroenterology Research and Practice)
Appendiceal pathology’s management has benefited in recent years from the advent of laparoscopic surgery. This study is to make a preliminary assessment of laparoscopic management of acute and complicated appendicitis in children after a few months of practice at the University Hospital Albert Royer, Dakar. This is a retrospective study of 22 cases of patients, all operated on by the same surgeon. The parameters studied were age, sex, clinical data and laboratory features, radiological data, and results of surgical treatment. The mean age of patients was 9.5 years with a male predominance. The series includes 14 cases of acute appendicitis and 8 complicated cases. Appendectomy anterograde is practiced in 81% of cases. Appendectomy was associated with peritoneal wash in 17 patients including 9 cases of acute appendicitis. Drainage of Douglas pouch is performed in 2 patients with complicated appendicitis; the average production was 300 cc of turbid liquids and any complications were not founded. An abscess of Douglas pouch is noted in 2 patients with complicated appendicitis undrained. These Douglas abscesses were treated medically. No conversion of laparotomy was performed in the series. After an average of 8 months no other problems were noted.